An investigation into the effectiveness of dynamic section control (inspection and rework) on the quality of the 3-series from the assembly plant at BMW (South Africa) (PTY.) Ltd. - Chantler, Jonathan (My University, 1996)
This research project is an investigation into the effectiveness of an inspect and rework system called dynamic section control which has the purpose of improving the assembly quality of the BMW-3 series manufacturing in the Rosslyn Plant just outside Pretoria in South Africa, The system was introduced into the assembly plant in February 1995 to improve the assembly quality of the vehicles as quickly as possible. The main motivation behind the need for this system was to bring the quality onto the same level as the German plants in order to become recognised in the international network of BMW's manufacturing plants along with the new manufacturing plant in the USA The origins of the dynamic section control system come from the Munich 3-series plant as well as being based on the principles of poka yoke, a quality philosophy devised by the quality expert from Toyota in Japan, Shigeo Shingo, Defects found on the assembly plant's line, identified by the quality auditor and information from the marketing department regarding warranty claims are entered onto a checklist which is used by reworkers in the plant to inspect and make good the defects that have been found. The checklist is updated on a weekly basis, hence its name: dynamic section control. Seven rework stations, in which the dynamic section control reworkers work, have been strategically positioned in the assembly plant which trims the painted bodies it receives from the paint shop, The effectiveness of the system has been measured by analysing the information from the daily audits as well as investigating the trend of vehicles If rving the assembly plant still requiring rework and repairs off-line. The analyses were divided into three distinct periods. The first being approximately 4 months before the introduction of :he dynamic section control system, and the second and third periods after the introduction of the system. The results show that the dynamic section control system have a positive influence in improving the assembly quality of the vehicles, especially reducing the number of recurring defects. The number of defects that have only occurred once in each of the periods has remained reasonably constant indicating that the system has no impact in reducing the random occurrence of "one-off" defects. Another significant finding was. the increase in the number of vehicles requiring Department of Mechanical Engineering, University of the Witwatersrand repair off-line, attributable to the assembly plant, after the vehicle has left the assembly line. This increase is probably the result of an increased quality awareness within the assembly plant, resulting in reworkers identifying an increasing number of defects for repair off-line. Other factors such as clearer identification of production goals, training and development of a proportion of the assembly plant's workers in the German plants lor three weeks, reorganizing of support. staff by installing "the right people in the right place" and reducing the number of model derivatives in the plant have also contributed to the enormous quality improvement achieved. Further development of the. dynamic section control system is recommended by installing a rework station within each team area, and including the actions of dynamic section control in the work content of that team. Currently, the system uses external workers which are not part of individual teams as the current sections overlap team areas. Finally, it is recommended that the work of the dynandc section control reworker be incorporated as a noma! function within the team and be rotated amongst the team members.
A project report submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Engineering. Johannesburg, 1996.
Keywords: Motor vehicles--Design and construction--Quality control; Motor vehicles--South Africa; Assembly-line methods--Quality control; BMW (South Africa) (Pty.) Ltd.